2019
DOI: 10.7554/elife.51603
|View full text |Cite
|
Sign up to set email alerts
|

A single regulator NrtR controls bacterial NAD+ homeostasis via its acetylation

Abstract: Nicotinamide adenine dinucleotide (NAD+) is an indispensable cofactor in all domains of life, and its homeostasis must be regulated tightly. Here we report that a Nudix-related transcriptional factor, designated MsNrtR (MSMEG_3198), controls the de novo pathway of NAD+biosynthesis in M. smegmatis, a non-tuberculosis Mycobacterium. The integrated evidence in vitro and in vivo confirms that MsNrtR is an auto-repressor, which negatively controls the de novo NAD+biosynthetic pathway. Binding of MsNrtR cognate DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…In most bacteria, NAD + is synthesized through a de novo synthesis pathway and salvage pathways I and/or II [ 43 ]. A conserved transcriptional regulator NrtR controls the expression of genes involved in NAD + biosynthesis [ 44 ]. In Mycobacterium smegmatis , mutation of the nrt R gene increases the expression of NAD + biosynthesis genes and intracellular NAD + level [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most bacteria, NAD + is synthesized through a de novo synthesis pathway and salvage pathways I and/or II [ 43 ]. A conserved transcriptional regulator NrtR controls the expression of genes involved in NAD + biosynthesis [ 44 ]. In Mycobacterium smegmatis , mutation of the nrt R gene increases the expression of NAD + biosynthesis genes and intracellular NAD + level [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…A conserved transcriptional regulator NrtR controls the expression of genes involved in NAD + biosynthesis [ 44 ]. In Mycobacterium smegmatis , mutation of the nrt R gene increases the expression of NAD + biosynthesis genes and intracellular NAD + level [ 44 ]. In P. aeruginosa , NrtR directly represses genes involved in the NAD + synthesis salvage pathway I, including pncA , pncB1 , nadE and nadD2 [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…This system consists of the ribosomal protein L13, RenU and eukaryotic-type protein kinase PknG, the last of which is essential for survival of Mycobacterium tuberculosis in host macrophages. Studies on African swine fever virus ASFV-DP(g5R) m 7 GTP -RNA [46,47] Pseudomonas aeruginosa PA4400 nd [50] Pseudomonas aeruginosa PA5176 nd [50] Pseudomonas aeruginosa NrtR na [42] Streptococcus suis NrtR na [43] Mycobacterium tuberculosis RenU NADH [45] Phytophthora sojae Avr3b NADH; ADP-ribose [39] Ralstonia solanacearum RipN NADH, NAD [38] nd, Not determined; na, not active.…”
Section: Nudix Proteins In Pathogenesismentioning
confidence: 99%
“…A high ADP-ribose level in the cell indicates active NAD turnover, which induces activation of expression of an NAD biosynthetic gene by inhibiting the repressor function of NrtR. It has also been shown that, in addition to ADP-ribose, post-translational acetylation of NrtR at lysine 134 plays an important role in this regulatory circuit given that mutation of K134 increased transcription of the nad operon and subsequently the cellular level of the cofactor [42]. An nrtR knockout reduces biofilm formation and attenuates virulence of Streptococcus suis , a leading agent of swine septicaemia [43].…”
Section: Nudix Proteins In Pathogenesismentioning
confidence: 99%
“…As well as fundamental functions within bacterial cells, they also come into play as genuine pathogenicity factors, as some Nudix proteins are secreted into host cells, where they disrupt host processes, such as the RipN effector from Ralstonia solanacearum that alters the NADH/NAD + ratio in plant cells [ 20 ], and they are also used by the oomycete pathogen Phytophthora to modify the plant immune system [ 21 ]. Interestingly, Nudix domain variants exist where the active site has been mutated and their basic nucleoside-binding function is used as a domain within a family of transcription factors, which are called Nudix-related transcriptional regulators (NrtRs) [ 22 ], the function of which have been confirmed experimentally [ 23 ].…”
mentioning
confidence: 99%